Analysis of Non-Performing Loans at Permata Bank for the 2008-2022 Period - Novan Ananda Ramadhan; Parningotan Sjiabat; Souza Al-Gibrani Nerva; Teguh Fachri Fahros (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to analyze trends & factors based on credit info system data on the NPL report at Bank Permata in 2008-2022. NPL fluctuated, increasing during the 2008-09 crisis. Economic downturn, high rates, & defaults are major contributors. Corporate loans affected by the crisis; consumer loans during the pandemic. The bank implemented measures: loan restructuring, risk management. Hence the need to improve credit decisions & risk management for a healthy portfolio.